Taxing Africa Coercion, Reform and Development - Moore, Mick. (London Zed Books, 2018)
Taxation has been seen as the domain of charisma-free accountants, lawyers and number crunchers ? an unlikely place to encounter big societal questions about democracy, equity or good governance. Yet it is exactly these issues that pervade conversations about taxation among policymakers, tax collectors, civil society activists, journalists and foreign aid donors in Africa today. Tax has become viewed as central to African development.
Keywords: Taxation